The farmer's benevolent trust : law and agricultural cooperation in industrial America, 1865-1945 - Woeste, Victoria Saker (The University of North Carolina Press, 1998)
Farmer''s Benevolent Trust: Law and Agricultural Cooperation in Industrial America, 1865-1945.
Keywords: California Associated Raisin Company.; California Associated Raisin Company; Agriculture, Cooperative -- Law and legislation -- United States -- History.; Raisin industry -- Law and legislation -- California -- History.; Coopératives agricoles -- Droit -- États-Unis -- Histoire.; Raisins secs -- Industrie -- Droit -- Californie -- Histoire.; LAW -- Administrative Law & Regulatory Practice.; Agriculture, Cooperative -- Law and legislation; Raisin industry -- Law and legislation; California; United States; Landbouwbedrijven.; Industrialisatie.; Samenwerkingsvormen (bedrijfseconomie); Juridische aspecten.; Landwirtschaftsgenossenschaft; Recht; USA; Agriculture, Cooperative -- Law and legislation -- United States.; Raisin industry -- California -- Law and legislation.; Geschichte 1865-1945.; cooperative farming; cooperatives; landbouw; agriculture; trusts; recht; cooperation; wetgeving; law; geschiedenis; legislation; vs; history; usa; samenwerking; raisins; rozijnen; california; agricultural cooperatives; Agricultural Law (Foreign); Rural History of North America; Agrarisch recht (buitenland); Rurale geschiedenis van Noord-Amerika; Electronic books.; History